Investigation and improvement of multi-resolution mutual-information-based registration - Dilla, Handini (2008)
Image registration algorithms adopting Mutual-Information-based technique implemented in multi-resolution scheme were developed and evaluated in this project. The algorithms, differing in its optimization techniques (the Powell's and Regular Step Gradient Descent optimizations) and its implementation (separate and combined optimizations), were evaluated for the speed and accuracy.